Team Building - Robert B Maddux (Viva Books, 2004)
Building a team is similar to building a house--you have to start from the ground up. A team is made up of individuals with different talents, skills, and personal working styles. Learning to work together as a group can be as challenging as it is rewarding. Team Building, one of Crisp's most popular Fifty-Minute Books, is a primer on how to formulate strong teams through a climate of open communication, trust, and accountability. Like building a house, the fourth edition takes readers step by step through the process from creative ways to encourage teamwork to tips for handling conflicts effectively.